Occurrence of chlorinated and brominated dioxins/furans, PCBs, and brominated flame retardants in blood of German adults - Fromme, Hermann; Hilger, Bettina; Albrecht, Michael; Gries, Wolfgang; Leng, Gabriele; Völkel, Wolfgang (International journal of hygiene and environmental health, 2016)
Persistent organic pollutants are widespread in the environment, and are associated with a particular health and ecological concern. The human body burden of polychlorinated dibenzo-p-dioxins and dibenzofurans (PCDDs/Fs), polybrominated dibenzo-p-dioxins and dibenzofurans (PBDDs/Fs), polychlorinated biphenyls (PCBs), polybrominated diphenylether (PBDEs), and hexabromocyclododecanes (HBCDs) was determined. Blood samples were collected in Germany, originating from 42 randomly selected subjects between 20 and 68 years old. The median (95th percentile) concentrations, expressed as WHO2005-TEQ for PCDD/PCDFs and dioxin-like PCBs, were 6.2 (19.1) pg/g l.w. and 4.1 (8.8) pg/g l.w., respectively. PBDDs/Fs were found with a median of 2.8 pgTEQ/g l.w. and a 95th percentile of 8.7 pgTEQ/g l.w. (using similar interim TEF values as for PCDDs/Fs) On a median basis, the contribution of PCDD/Fs, dioxin-like PCBs, and PBDDs/Fs to total TEQ were 47%, 31%, and 21%, respectively. The sum of the 6 non-dioxin-like PCBs exhibited a median of 267ng/g l.w. and a 95th percentile of 834ng/g l.w. The median value for the sum of six tetra- to hepta-PBDE congeners was 1.7ng/g l.w. (95th percentile: 4.9ng/g l.w.). BDE 209 was the most abundant congener with a median of 1.8ng/g l.w. HBCDs were only found in some samples, and concentrations ranged between the limit of detection (5ng/g l.w.) and the limit of quantification (16ng/g l.w.). Results for PBDEs and HBCDs are comparable to other European studies. Our study demonstrated that the body burden of PCDD/Fs and PCBs declined continously since the last three decades, but exposure may exceed precautionary guideline levels.